Peran Penggunaan Bahasa Indonesia dalam Proses Pelayanan terhadap Kualitas Layanan dan Kepuasan Nasabah PT Asuransi Ramayana Tbk. - Meilina Widya Dali; Keyla Zakaria; Sintia Yusuf; Anggriani Putri Abbas; Suci Ramadhani S. Tantu; Adelia Putri Mooduto; Selvia I. Kai; Afriliyani Putri Manunu; Fazrillah Lajunaidi; Risna Fausiah; Renaldi Saliko; Alim Bahruh Ulum Ruchban; Fajri Aditya Van Solang; Yunus M. Olii (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Indonesian plays a crucial role in the service sector, particularly in the insurance industry, which demands clarity and accurate communication. This study aims to analyze the influence of Indonesian language use on the service quality of PT Asuransi Ramayana Tbk. and its impact on customer satisfaction. The research method used is descriptive with a qualitative approach. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation related to the insurance service process. The research subjects included employees and customers of PT Asuransi Ramayana Tbk who were directly involved in service activities. The results show that the use of clear, polite, and easy-to-understand Indonesian language contributes positively to improving service quality. Indonesian language not only functions as a communication tool but also as a means of building trust, clarifying policy information, and minimizing misunderstandings between the company and customers. Thus, optimizing the use of Indonesian language in insurance services has a significant impact on the level of customer satisfaction at PT Asuransi Ramayana Tbk.